2021
DOI: 10.3389/fnins.2021.654957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thresholding on Voxel-Wise Correspondence of Breath-Hold and Resting-State Maps of Cerebrovascular Reactivity

Abstract: Functional magnetic resonance imaging for presurgical brain mapping enables neurosurgeons to identify viable tissue near a site of operable pathology which might be at risk of surgery-induced damage. However, focal brain pathology (e.g., tumors) may selectively disrupt neurovascular coupling while leaving the underlying neurons functionally intact. Such neurovascular uncoupling can result in false negatives on brain activation maps thereby compromising their use for surgical planning. One way to detect potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 96 publications
(211 reference statements)
0
7
0
Order By: Relevance
“…We assess the agreement of hemodynamic timing estimates derived from data that contained a breathhold task and from data that only contained resting-state (spontaneous) fluctuations, to understand how similar these timing estimates are in an individual. To further interpret our assessment of the agreement, we applied amplitude thresholds (Chang et al, 2008; Fesharaki et al, 2021) and different levels of smoothing of the input data, hypothesizing that signal-to-noise factors would modulate the absolute agreement of hemodynamic timing estimates. We also investigated which areas of the brain (if any) had the highest agreement, to help provide anatomical insight into what may be driving agreement or disagreement.…”
Section: Introductionmentioning
confidence: 99%
“…We assess the agreement of hemodynamic timing estimates derived from data that contained a breathhold task and from data that only contained resting-state (spontaneous) fluctuations, to understand how similar these timing estimates are in an individual. To further interpret our assessment of the agreement, we applied amplitude thresholds (Chang et al, 2008; Fesharaki et al, 2021) and different levels of smoothing of the input data, hypothesizing that signal-to-noise factors would modulate the absolute agreement of hemodynamic timing estimates. We also investigated which areas of the brain (if any) had the highest agreement, to help provide anatomical insight into what may be driving agreement or disagreement.…”
Section: Introductionmentioning
confidence: 99%
“…Biswal , 2008;Kannurpatti et al, 2014); in fact, the simplicity of RS fMRI makes it particularly suitable in clinical settings for more vulnerable populations (Fesharaki et al, 2021) and extreme cases such as loss of consciousness (Golestani et al, 2016). Previous studies have even suggested that RSF maps would be better estimators of physiological changes given the high regional agreement between the two measures (De Vis et al, 2018;Kannurpatti & Biswal, 2008;Kannurpatti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…An easier setup and better patient tolerance of RS fMRI, compared to studies evoking vasodilatory responses using breathing or gas-inhaled challenges, are often cited as reasons to adopt RSF metrics as a proxy for CVR (Fesharaki et al, 2021; Golestani et al, 2016; Kannurpatti & Biswal, 2008; Kannurpatti et al, 2014); in fact, the simplicity of RS fMRI makes it particularly suitable in clinical settings for more vulnerable populations (Fesharaki et al, 2021) and extreme cases such as loss of consciousness (Golestani et al, 2016). Previous studies have even suggested that RSF maps would be better estimators of physiological changes given the high regional agreement between the two measures (De Vis et al, 2018; Kannurpatti & Biswal, 2008; Kannurpatti et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of variability in respiration and its effect on BOLD fMRI as a CVR biomarker is a new discovery [ 107 , 111 ]. However, given that the outcomes of resting-state approaches are unpredictable, further research is necessary before they can completely replace BH procedures [ 112 ].…”
Section: Cerebrovascular Reactivity Mapping (Cvr) For Nvu Detection I...mentioning
confidence: 99%